FOLK MUSIC AT RHYTHMICS LESSONS AS A MEANS FOR PERSONALITY DEVELOPMENT OF SCHOOLCHILDREN - Бабич, С.С.; Балжанова, А.М. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2021)
The article reveals the interrelation of music and dance at rhythmics lessons at school. The value of music is considered as a way of positive influence on pupils` psychoemotional condition that forms the basis for development of multiculturalism and aesthetic taste. The process of listening to folk music concentrates attention, develops creative imagination, increases activity and working efficiency. The article presents choreography art along with folk music.
Keywords: folk music; choreography; rhythmics lesson; development of personality; creative development